Laccase and peroxidase isoenzymes during leaf litter decomposition of Quercus ilex in a Mediterranean ecosystem - Di Nardo, C; Cinquegrana, A; Papa, S; Fuggi, A; Fioretto, a (Soil Biology and Biochemistry, 2004)
The dynamics of leaf litter decomposition of Quercus ilex (L.) were investigated over a 2 year period by determining the activities and isoenzyme distribution of laccases and peroxidases. The analysis of isoenzymes was performed by isoelectric focusing on high stability pH gradients with high resolving power. The preparation of zymograms was carried out using the leaf litter extract without previous concentration. During litter decomposition, laccase and peroxidase activities changed as well as the type and number of enzyme isoforms. The activities of both enzymes were low (%0.017 and %0.031 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively) in ﬁrst year and increased in October–January of the second year of litter decay. The highest activities measured after 15–18 months of litter exposure (0.37G0.03 and 0.19G0.02 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively), showed that litter chemical composition affected the growth of ligninolytic microbial community. The activation energy for laccase and peroxidase reactions also changed during decomposition: the highest values (55G6 kJ molK1 for laccase and 60G6 kJ molK1 for peroxidase) occurred in autumn–winter, even if spatial changes were evidenced. Some enzyme isoforms (pIZ5.3 and 5.5 for laccase and pIZ5.0 and 5.1 for peroxidase, respectively), contributed more than others to the overall laccase and peroxidase activity, suggesting that some ligninolytic species bloomed in particular seasons of the year, even if other species with similar functional activities colonized the litter.
Keywords: Enzyme activity; isoelectrofocusing; laccase; litter decomposition; peroxidase

Laccase and peroxidase isoenzymes during leaf litter decomposition of Quercus ilex in a Mediterranean ecosystem - Di Nardo, C.; Cinquegrana, A.; Papa, S.; Fuggi, A.; Fioretto, A. (Soil Biology and Biochemistry, 2004)
The dynamics of leaf litter decomposition of Quercus ilex (L.) were investigated over a 2 year period by determining the activities and isoenzyme distribution of laccases and peroxidases. The analysis of isoenzymes was performed by isoelectric focusing on high stability pH gradients with high resolving power. The preparation of zymograms was carried out using the leaf litter extract without previous concentration. During litter decomposition, laccase and peroxidase activities changed as well as the type and number of enzyme isoforms. The activities of both enzymes were low (%0.017 and %0.031 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively) in ﬁrst year and increased in October–January of the second year of litter decay. The highest activities measured after 15–18 months of litter exposure (0.37G0.03 and 0.19G0.02 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively), showed that litter chemical composition affected the growth of ligninolytic microbial community. The activation energy for laccase and peroxidase reactions also changed during decomposition: the highest values (55G6 kJ molK1 for laccase and 60G6 kJ molK1 for peroxidase) occurred in autumn–winter, even if spatial changes were evidenced. Some enzyme isoforms (pIZ5.3 and 5.5 for laccase and pIZ5.0 and 5.1 for peroxidase, respectively), contributed more than others to the overall laccase and peroxidase activity, suggesting that some ligninolytic species bloomed in particular seasons of the year, even if other species with similar functional activities colonized the litter.
Keywords: Enzyme activity; isoelectrofocusing; laccase; litter decomposition; peroxidase

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S.; Farnet, A. M.; Tagger, S.; Petit, J. Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S; Farnet, A M; Tagger, S; Petit, J Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Laccase activity of forest litter - Criquet, S.; Tagger, S.; Vogt, G. (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity
Keywords: Extraction; laccase; litter

Laccase activity of forest litter - Criquet, S; Tagger, S; Vogt, G (Soil Biology and Biochemistry, 1999)
Laccases are blue-copper enzymatic proteins involved in the transformation of polyphenolic compounds, such as lignin, into forest litter. A method to measure their activity was developed using an evergreen oak litter as a model system. We considered factors that aect the extraction of these enzymes and the measurement of their activity. The factors studied included powdering of the leaves, adding polyvinylpolypyrrolidone or Tween 80, adsorption of enzymes on centrifugation pellets, concentration of the extracts, nature and molarity of the extraction solvent, amount of powdered leaves used for enzymatic extraction, extraction time, pH, and temperature during the measurement of the activity
Keywords: Extraction; laccase; litter